Fishing for coherence : Proceedings of the workshop on policy coherence for development in fisheries - Andrews-Chouicha, Emily; Consolati, Maria; Organisation for Economic Co-operation and Development (Paris : OECD, 2006)
Some 500 million USD are spent annually on fisheries development projects. But fisheries access agreements and trade policies are sometimes applied in ways that dampen developing countries' ability to benefit fully from their rich marine resources. Also, many development projects do not pay sufficient regard to the sustainability issues that are a key for the future of the fishing sector. This publication, a compilation of papers from the Workshop on Policy Coherence for Development in Fisheries, addresses these issues.--Publisher description
Policy coherence and fisheries : from crisis to recovery : a synthesis of the workshop deliberations -- pt. 1. Opening of the workshop and keynote addresses -- pt. 2. The role of fisheries access agreements : perspectives for developing and developed countries -- pt. 3. The role of trade policies and how to benefit developing and developed countries' consumers -- pt. 4. What role does development assistance play in ensuring good governance of fisheries and aquaculture in developing countries and what have we achieved?
Proceeding of the workshop held in Paris, April 24-25, 2006, convened jointly by the Committee for Fisheries and the Development Assistance Committee of OECD
Includes bibliographical references (p.243-253)